A novel approach on neutrosophic crisp sets - A. Johnny, Saied; Ibrahim Nasser, Hashmiya (Al-Qadisiyah Journal of Pure Science, 2018)
The focus of this paper is to introduce a new type of neutrosophic crisp sets as the neutrosophic crisp soft sets and which is the generalization of an ordered triple in the definition of Salama set’s [9]. After given the fundamental definitions of generalized neutrosophic crisp set operations, we obtain several properties and we discussed some theorems in this concept. Finally , the concept to the neutrosophic crisp soft lattices.